Strategi Guru dalam Mengatasi Tindakan Perundungan pada Siswa di Kelas VI SD Al-Islam - Nuril Ardaniyah; Aan Widiyono (BASICA, 2023)
Bullying is a criminal act that can occur in the world of education. This event sparked the interest of researchers to conduct research. The purpose of this research is none other than to shed light on teacher’s strategies to anticipate and reduce the level of bullying in schools. This research used a qualitative descriptive research appoarch with a case study type. The data collection techniques in this study used observational techniques, interviews with class VI teachers, class VI student, and school principals, and documentation as data collection materials obtained. The test validity pf data using the triangulation technique and source triangulation. This research was conducted at SD Al-Islam Pengkol Jepara from August 4 2023 to August 7 2023. The research findings show that teachers have several strategies to overcome acts of bullying toward student. Namely giving advice, counseling, mental reinforcement to the victims, providing sanctions or punishments, socialization takes place. From the results, it can be concluded that principals and class teachers play an important role in dealing with bullying cases at school.Bullying is a criminal act that can occur in the world of education. This event sparked the interest of researchers to conduct research. The purpose of this research is none other than to shed light on teacher’s strategies to anticipate and reduce the level of bullying in schools. This research used a qualitative descriptive research appoarch with a case study type. The data collection techniques in this study used observational techniques, interviews with class VI teachers, class VI student, and school principals, and documentation as data collection materials obtained. The test validity pf data using the triangulation technique and source triangulation. This research was conducted at SD Al-Islam Pengkol Jepara from August 4 2023 to August 7 2023. The research findings show that teachers have several strategies to overcome acts of bullying toward student. Namely giving advice, counseling, mental reinforcement to the victims, providing sanctions or punishments, socialization takes place. From the results, it can be concluded that principals and class teachers play an important role in dealing with bullying cases at school.